Scientific Illustration: from Informational Support to a Culture of Participation - D. K. Lisovsky (Дискурс)
Introduction. The visualization of scientific knowledge dating back more than one century, nevertheless, for each new generation of scientists it turns out to be a topic of acute interest. This is due to constantly changing technical and technological means of presenting scientific data, as well as a change in the communicative space of science itself. Modern scientific life and the activities of scientists are constantly in the zone of acute conflict between preserving the principles of elitism, integrity, exclusivity, and the principles of openness, general accessibility, and massization that are equally necessary for its existence. An analysis of the place and role of visualizing scientific knowledge allows us to discover resources and models for managing this conflict in the field of scientific communication.Methodology and sources. The culturological approach in describing the stages of scientific illustration development, as well as methods of comparative, typological, contextual analysis became the methodological principles of the research. For writing the work we used sources that allowed us to analyze the history of formation and the current state of scientific illustration, as well as a variety of types of visualization of scientific knowledge. Information sources were the research of Science Art in the context of solving the problems of popularization of scientific knowledge.Results and discussion. The object of this study is scientific illustration as a visual practice aimed at overcoming the boundaries between science, art and education. The development of scientific illustration includes 4 fundamentally different periods: the use of illustration as a tool for working with information that is difficult for the human eye (primarily in the interests of medicine); with the advent and development of photography, the drift of scientific illustration in the direction of fine art with the increasing importance of the artist (painter), and not the subject of the image; with the complexity of the species diversity of the visual representation of scientific information, the stimulation of the figurative component in the search and presentation of scientific knowledge as a specific task of scientific illustration; scientific illustration as a necessary component of the process of convergence of scientific-cognitive and artistic-visual techniques in scientific communication.Conclusion. In the 21st century, scientific illustrations are technological products created jointly by scientists, artists, their direct customers and society as a whole. Representing one of the types of visualization of scientific knowledge, scientific illustration performs its own educational and communicative functions. Liberalization of image tools, development of educational comics, information visualization and data visualization, as well as the appearance of SciArt movement – all these factors make the problem of professional selfidentification of scientific illustrators urgent.